Tie me up! Tie me down! - Morricone, Ennio 1928-2020 (The Criterion Collection, 2014)
DIRECTOR-APPROVED EDITION:New 2K digital restoration, supervised by director Pedro Almodo̒var and executive producer Agusti̒n Almodo̒var, with 5.1 surround DTS-HD Master Audio soundtrack on the Blu-rayNew documentary on the making of the film, featuring interviews with Pedro Almodo̒var; Agusti̒n Almodo̒var; actors Antonio Banderas, Victoria Abril, Loles Leo̒n, and Rossy de Palma; production manager Esther Garci̒a; and cinematographer Jose̒ Luis AlcaineNew interview with Almodo̒var collaborator and Sony Pictures Classics copresident Michael BarkerConversation from 2003 between Pedro Almodo̒var and BanderasFootage from the filmĐs 1990 premiere party in MadridNew English subtitle translationPLUS: A booklet featuring a 1990 piece about the film by Pedro Almodo̒var, a conversation between critic Kent Jones and filmmaker Wes Anderson, andan interview with Almodo̒var from 1989New cover by Malika Favre